Akhlak Bergaul Muslim yang Baik dalam Islam Menurut Sayyid Muhammad - Yulfani (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2021)
As a religion, Islam is a universal and eternal religion that provides guidelines for all human beings to reachh inner and outer happiness as well as the world and the hereafter. Islam is a religion that proritizes morality. Morals are a reflection of a person’s sprit, good or bad, morals are a strong indicator of his happiness. A muslim who believes, of course, always acts in accordance with Islamic guidance in life to avoid self from benefit, in associating with a good muslim, of course, in associating with morals in his asspciation so that association in his social environment, such as being with one human being with another human, cannot be separated from the will, needs complement each other. This is where Sayyid Muhammad trough his thoughts in the book Tahliyah wa at Targhib Fii Tarbiyah wa at tahdzib opens the door of association for muslims so that there is harmony in the association.